Protective action of leaves of Epipremnum aureum in gastric ulcer prevention induced by ethanol in rats (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The study investigated the gastroprotective effects of Epipremnum aureum leaf extracts against ethanol-induced gastric ulcers in rats. Dosages of 200 mg/kg and 400 mg/kg of the methanolic extract were administered, with omeprazole used as the positive control. The methanol extract significantly protected the gastric mucosa from ethanol-induced damage, suggesting cytoprotective potential. Ethanol exposure led to a decrease in plasma antioxidant enzyme levels and increased lipid peroxidation, indicating oxidative stress. However, rats treated with the higher extract dose (400 mg/kg) and omeprazole showed significant improvements, with increased SOD and CAT levels, reduced lipid peroxidation, and a lower ulcer index compared to the untreated ulcer group. Histopathological analysis revealed severe gastric mucosal damage in the ethanol-only group, while the high-dose extract and omeprazole groups maintained normal gastric architecture with minimal inflammation. These findings suggest that Epipremnum aureum methanolic extract exhibits potent gastroprotective effects, potentially due to its rich phytochemical profile, including flavonoids, tannins, and alkaloids, supporting its use as a natural remedy for gastric ulcers.